Husbands' Plan to Participate in Birth Preparedness and Complication Readiness in Haramaya Health and Demographic Surveillance System Site, Eastern Ethiopia: A Community-Based Cross-Sectional Study - Sufian, Seada; Kure, Mohammed Abdurke; Dheresa, Merga; Debella, Adera; Balis, Bikila; Roba, Kedir Teji (Frontiers in Public Health, 2022)
Background Partner involvement in maternal health services utilization remains a major public challenge in the developing world. Strategies of involving men in maternal health services are a critical and proven intervention for reducing maternal and neonatal mortality by ensuring safe delivery and reducing complications during childbirth. Moreover, the husbands' involvement during pregnancy helps their spouses to make timely decisions and avoid maternal delays, especially first and second delays. Although birth and complication readiness have been studied in developing countries such as Ethiopia, almost all previous researchers were focused primarily on women participants. Therefore, we aimed to investigate factors associated with husband involvement in birth preparedness and complication readiness plan in Haramaya Health and Demographic Surveillance site, Eastern Ethiopia. Methods A community-based cross-sectional study was conducted from March 1 to 30, 2020 among men whose wives were pregnant in Haramaya Health and Demographic Surveillance (HDSS) site in Eastern Ethiopia. The calculated sample size was 653, however while contacting 653 husbands only 630 had given the full interview, hence 630 respondents were remained in the analysis. Participants were approached through a systematic sampling technique. Data were collected using a pre-tested structured questionnaire through a face-to-face interview, and entered into Epidata version 3.1 and analyzed using SPSS version 22 (IBM SPSS Statistics, 2013). The prevalence was reported using proportion with 95% Confidence Interval (CI) and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using an adjusted odds ratio (AOR) with 95%CI. Statistical significance was declared at p < 0.05. Results Overall, the prevalence of the husband's plan to participate in birth preparedness and complication readiness was 59.6% (95%CI:56–64%). In the final model of multivariable analysis, predictors like husband's knowledge of birth preparedness and complication readiness [AOR = 4.18, 95%CI:2.05, 8.51], having a discussion with spouse on the place of delivery [AOR = 6.84, 95% CI: 4.17, 11.22], husband's knowledge of danger signs during labor and delivery [AOR = 3.19, 95 % CI: 1.52, 6.71], and making a postpartum plan[AOR = 2.30, 95 % CI: 1.38, 3.85] were factors statistically associated with husband's plan to participate in birth preparedness. Conclusions This study pointed out that two in every five husbands failed to plan birth preparedness and complication readiness. As a result, all stakeholders should emphasize male partners' education in terms of birth preparedness and complication readiness, as well as knowledge of danger signs during labor and delivery. They should also encourage male partners to discuss a place of delivery and have a postpartum plan in place to reduce potential complications related to labor and delivery.